The Impact of Health Transformation Plan on Deductions Imposed on Imam Khomeini Hospital Complex's Bills - Alimohammad Mosadeghrad; Mahnaz Afshari; Rahman Nasrolahi; Sareh Daneshgar; Rasoul Corani Bahador (Tehran University of Medical Sciences, 2018)
Background: Insurance companies sometimes do not reimburse hospitals completely. Reducing the amount of deduction of bills increases hospital's income and efficiency. This study compares the deductions imposed by social insurance organization on Imam Khomeini hospital's bills before and after the implementation of health transformation plan.   Material and Methods: Data of this descriptive-descriptive study calculated from the deductions applied to the hospital of outpatient and inpatient bills of social insurance organization in second six months of 2013 (before implementation of health transformation plan) and the same time of 2014 (after implementation of of health transformation plan). This quasi experimental study was conducted using the data. Data was analyzed by SPSS software using paired t test.   Results: The bill deductions in the second six months of 2013 compare to the same time in 2014 were 2.9 and 11.1 percent, respectively. Hospital bill deductions increased 282.8 percent after the health transformation plan implementation. The deductions on inpatients and outpatients records increased 6 and 12 times, respectively. Most deduction was imposed on surgical and laboratory bills in 2013 and on radiotherapy, chemotherapy and hoteling bills in 2014.   Conclusion: Deductions of hospital bills extremely increased from social insurance organization after implementation of health transformation plan. In order to identify deductions causes, providing related education to staff and physicians and relative process improvement are necessary.